Evaluation of aerodynamic coefficients of supercritical airfoil NASA sc(2) 0712: A comparative study of 2D and 3D flow models with experimental validations - Šukunda Teodora; Svorcan Jelena; Ivanov Toni (FME Transactions)
This study presents a comparative numerical analysis of 2D and 3D compressible, turbulent flows around the supercritical airfoil NASA sc(2) 0712 at Mach number M = 0.5 using the finite volume method implemented in ANSYS Fluent, focusing on the estimation of drag coefficients in relation to existing experimental data. In addition, different types of computational grids and turbulence models are tested. The investigation aims to highlight the discrepancies observed between the two modeling approaches and their implications for aerodynamic performance predictions. Through rigorous numerical simulations and validation against experimental results, we demonstrate that 2D models often yield overestimated drag values due to simplified flow assumptions. In contrast, 3D simulations provide a more accurate representation of fluid behavior, resulting in closer alignment with experimental findings. By performing spatial computations of turbulent flow around a supercritical airfoil, it is possible to reduce the relative error of drag coefficients by less than 10%.